Implementation of Aqidah and Akhlak Learning in Forming the Character of Students at MTs Al-Islami Bujuk Agung in the 2024/2025 Academic Year - Miftahul Jannah; Subiantoro Subiantoro; Ahmad Tamyiz (Global Education Journal, 2025)
Aqidah Akhlak learning is a strategic instrument to instill the belief in monotheism while shaping the noble behavior of students to answer the challenges of moral degradation in the digital era. This study aims to describe and analyze in depth the implementation of Akidah Akhlak learning in shaping the character of students at MTs Al-Islami Bujuk Agung in the 2024/2025 academic year, as well as to identify supporting and inhibiting factors. This study uses a descriptive qualitative approach. Data were collected through participant observation techniques, in-depth interviews with madrasah principals, teachers, and students, as well as documentation studies. Data analysis was carried out systematically through data reduction, data presentation, and drawing conclusions, while the validity of the data was tested using source and technique triangulation techniques. The results of the study showed that the implementation of Akidah Akhlak learning was carried out through three main integrated stages. First, planning is carried out by compiling a lesson plan that maps character values to each basic competency. Second, the implementation emphasizes varied methods, teacher role models through the 5S culture, and religious habits such as congregational Dhuha prayers and wirid. Third, the evaluation is carried out authentically, covering cognitive, affective, and psychomotor aspects through behavioral observation journals and assessments of worship practices. This implementation is effective in forming religious, honest, disciplined and polite characters. However, the aspects of hard work and creativity still require further strengthening. The main supporting factors include consistent teacher role models and a religious school environment. On the other hand, inhibiting factors include the negative influence of gadgets (social media), lack of parental supervision at home, and limited infrastructure such as the capacity of places of worship and interactive media. This study concludes that optimal character formation requires ongoing synergy between schools, families, and strengthening of a digital literacy culture.